In vitro characterisation of SARS‐CoV‐2 and susceptibility of domestic ferrets (Mustela putorius furo). Issue 2 (29th January 2021) - Marsh, Glenn A.; McAuley, Alexander J.; Brown, Sheree; Pharo, Elizabeth A.; Crameri, Sandra; Au, Gough G.; Baker, Michelle L.; Barr, Jennifer A.; Bergfeld, Jemma; Bruce, Matthew P.; Burkett, Kathie; Durr, Peter A.; et al.
Abstract: Severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) is an emerging virus that has caused significant human morbidity and mortality since its detection in late 2019. With the rapid emergence has come an unprecedented programme of vaccine development with at least 300 candidates under development. Ferrets have proven to be an appropriate animal model for testing safety and efficacy of SARS‐CoV‐2 vaccines due to quantifiable virus shedding in nasal washes and oral swabs. Here, we outline our efforts early in the SARS‐CoV‐2 outbreak to propagate and characterize an Australian isolate of the virus in vitro and in an ex vivo model of human airway epithelium, as well as to demonstrate the susceptibility of domestic ferrets ( Mustela putorius furo ) to SARS‐CoV‐2 infection following intranasal challenge.